Atividade cicatrizante do extrato bruto de Arrabidaea chica (Humb. & Bonpl.) verlot - Jorge, Michelle Pedroza, 1981- (2008)
Orientadores: João Ernesto de Carvalho, Mary Ann Foglio, Lucia Tasca Gois Ruiz